Transcriptomic, Proteomic, and Metabolic Profiles of Catalpa bungei Tension Wood Reveal New Insight Into Lignin Biosynthesis Involving Transcription Factor Regulation - Xiao, Yao; Ling, Juanjuan; Yi, Fei; Ma, Wenjun; Lu, Nan; Zhu, Tianqing; Wang, Junhui; Zhao, Kun; Yun, Huiling (Frontiers in Plant Science, 2021)
Lignin is a complex polymer in plant cell walls whose proportion is second only to that of cellulose and plays an important role in the mechanical properties of wood and stress resistance of plants. Here, we induced tension wood (TW) formation in Catalpa bungei by artificial bending and analyzed the lignin metabolism of the TW. LC-MS analysis showed that a significantly higher content of coniferyl aldehyde was observed in the TW cell wall than in the opposite wood (OW) and normal wood (NW) cell walls. TW had significantly lower contents of coniferyl alcohol than OW and NW. Raman spectroscopy results indicated that TW had lower total lignin than OW and NW. The transcription and translation levels of most of the differentially expressed genes involved in lignin monomer biosynthesis indicated upregulation in TW/OW and TW/NW. We found no significant difference in the transcription levels of three CADs between TW and OW or between NW, but their translation levels were significantly downregulated in TW, suggesting posttranscriptional control for CAD. We predicted and analyzed transcription factors that could target differentially expressed genes involved in lignin monomer biosynthesis in TW. Based on the analysis of the relationships of targeting and coexpression, we found that NAC (evm.model.group1.695) could potentially target 4CLs and CCoAOMT, that HD-Zip (evm.model.group7.1157) had potential targeting relationships with CCoAOMT, F5H and CCR, and that their expression levels were significantly positive. It is speculated that the upregulation of NAC and HD-ZIP transcription factors activates the expression of downstream target genes, which leads to a significant increase in coniferyl aldehyde in TW. However, the decrease in total lignin in TW may be caused by the significant downregulation of CAD translation and the significant decrease in precursors (coniferyl alcohol). Whether the expression of CAD genes is regulated by posttranscriptional control and affects TW lignin metabolism needs further study.